TNFα in liver fibrosis - Yang, Yoon Mee (Curr Pathobiol Rep, 2015)
Hepatocyte death, inflammation, and liver fibrosis are the hallmarks of chronic liver disease. Tumor necrosis factor-α (TNFα) is an inflammatory cytokine involved in liver inflammation and sustained liver inflammation leads to liver fibrosis. TNFα exerts inflammation, proliferation, and apoptosis. However, the role of TNFα signaling in liver fibrosis is not fully understood. This review highlights the recent findings demonstrating the molecular mechanisms of TNFα and its downstream signaling in liver fibrosis. During the progression of liver fibrosis, hepatic stellate cells play a pivotal role in a dynamic process of production of extracellular matrix proteins and modulation of immune response. Hepatic stellate cells transdifferentiate into activated myofibroblasts in response to damaged hepatocyte-derived mediators and immune cell-derived cytokines/chemokines. Here, we will discuss the role of TNFα in hepatic stellate cell survival and activation and the crosstalk between hepatic stellate cells and hepatocytes or other immune cells, such as macrophages, dendritic cells, and B cells in the development of liver fibrosis.